Mineral deficiency in cattle of Roraima, Brazil. IV. Magnesium, sodium and potassium - Sousa, Júlio César de; Gonçalves, Eli Moraes; Viana, José de Alencar C.; Darsie, Gilfredo (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted to verify the mineral levels in beef cattle from six regions of northeast Roraima Federal Territory, Brazil. The soil, forage, and bovine tissue (blood, bone) were collected during the wet and dry seasons of the year. Only the soil from Surrão region showed medium level of Mg (0.500 meq/100g) all the others presented low levels. Soil K was at medium level in Caumé region (65 ppm), and low in all the other five regions. Soil Na levels were in a range from 47 ppm to 102 ppm. Forage Mg was sufficient to meet the requirements of growing and finishing steers, but was apparently deficient for lactating cows in five of six regions studied. Forage Na and K levels were low in all six regions. The levels of Mg, Na and K in the forages were significantly (P<0.05) lower during the dry season than during the wet season. In cultivated forage Mg levels, were sufficient to meet the requirements of beef cattle and in the native species were adequate only for growing and finishing steers. Magnesium plasma levels in cattle were normal in both seasons. Rib bone ash Mg means were low and ranged from 0.32% to 0.44% in the lactating cows and form 0.28% to 0.47% in the other animals.